When Seeing Isn't Believing - Current Multimedia Authentication Technologies and Their Applications - Zhu, Bin Benjamin; Swanson, Mitchell D.; Tewfik, Ahmed H. (IEEE Signal Processing, 2004)
Inherent properties of digital multimedia may be readily exploited to generate manipulated signals and forgeries. We present a review of current technologies for multimedia authentication and tamper detection. Integrity verification challenges and general requirements for multimedia authentication technologies are examined. Two major types of multimedia authentication, i.e., hard authentication and soft authentication, are discussed. Detailed descriptions on current systems in the literature are included for each authentication category.